The influence of fertilizer type and time of application on growth and forage productivity of mung bean - MOHAMMEDALTOM, ARD ALSHAM ADAM; DAGASH, YASSIN MOHAMED IBRAHIM (Asian Journal of Agriculture, 2017)
Mohammedaltom AAA, Dagash YMI. 2017. The effect of fertilizer type and time of application on growth and forage productivity of mung bean. Asian J Agric 1: 22-28. A field experiment was conducted on April 3, 2016, at the Demonstration Farm of College of Agricultural Studies, Sudan University of Sciences and Technology, Shambat, Khartoum, Sudan to study the effect of some fertilizers and their time of application on growth and forage productivity of mung bean. The treatments were arranged factorially in split-plot trial with four replications. Application time was assigned to the main plot as three times of application: before sowing, with sowing and after sowing. Types of fertilizers as the sub plot including four types of fertilizers: without fertilizer (control), 50 kg ha-1 (organic manure), 100 kg ha-1 (diammonium phosphate), and 10 L ha-1 (humic acid). Different characters were measured include plant height (cm), stem thickness (cm), number of branches/plant, number of leaves/plant, fresh weight/plant (g) as well as dry weight/plant (g). The results revealed that there is a highly significant difference for types and application time of fertilizers and their interaction on plant height, number of leaves, and fresh forage and dry forage. Highly significant differences (p â‰¤ 0.01) were recorded in types of fertilizers and interaction between different application time and types of fertilizers for number of branch and significant difference (p â‰¤ 0.05) of application time for number of branch and stem diameter. There was no significant difference in types of fertilizers for stem diameter. The highest height of the plant (28.78 cm), the highest number of branches/plant (9.37), the maximum stem diameter (6.43 cm), the largest number of leaves/plant (31.69), the best fresh weight (815 kg ha-1) and dry weight (161 kg ha-1) were recorded for the treatment of 50 kg ha-1 organic manure applied after sowing.